PENGARUH PENAMBAHAN ABU SISA PEMBAKARAN BATUBARA PADA MEDIA TANAM TERHADAP PERTUMBUHAN TANAMAN CABAI MERAH (Capsicum annum L) - Yustina Hapida (Jurnal Biota, 2015)
The research on the effect of adding coal ash residue in the planting media on the growth of Chili (Capsicum annum L) has been carried out, the purpose of the study was to determine the effect of coal ash mixed in the planting medium on the growth of Chili (C. annum L). This method was used a completely randomized experiment (RAL) consists of 7 treatmens with 3 replications. P0 (as a control), P1 (medium mixed with 2 grams of residual ash coal) P2 (4gr), P3 (6gr), P4 (8 g), P5 (10gr), P6 (12gr). Parameters measured were plant height, root length, shoot fresh weight, shoot dry weight, root fresh weight, root dry weight, and time when of the first fruit is appear. The data were analyzed with F test, the results showed that the coal ash residue has no real effect on the growth parameters, the maximum effect of the dose is at P5 10gr. The data obtained on plant height parameter are 39.67 cm, 25 cm root length, shoot fresh weight 16.40 grams, 3.38 gram wet weight root, shoot dry weight of 3.1 grams, 1,1gr root dry weight and the appearance of the first fruit is on P4 that 52.3 days.